Statin Use and Mortality among Patients Hospitalized with Sepsis: A Retrospective Cohort Study within Southern California, 2008–2018 - Brannen Liang; Su-jau T. Yang; Kenneth K. Wei; Albert S. Yu; Brendan J. Kim; Michael K. Gould; John J. Sim (Critical Care Research and Practice)
Background. Despite early goal-directed therapy, sepsis mortality remains high. Statins exhibit pleiotropic effects. Objective. We sought to compare mortality outcomes among statin users versus nonusers who were hospitalized with sepsis. Methods. Retrospective cohort study of patients (age ≥18 years) during 1/1/2008–9/30/2018. Mortality was compared between statin users and nonusers and within statin users (hydrophilic versus lipophilic, fungal versus synthetic derivation, and individual statins head-to-head). Multivariable Cox regression models were used to estimate hazard ratios (HR) for 30-day and 90-day mortality. Inverse probability treatment weighting (IPTW) analysis was performed to account for indication bias. Results. Among 128,161 sepsis patients, 34,088 (26.6%) were prescribed statin drugs prior to admission. Statin users compared to nonusers had a 30-day and 90-day mortality HR (95% CI) of 0.80 (0.77–0.83) and 0.79 (0.77–0.81), respectively. Synthetic derived statin users compared to fungal derived users had a 30- and 90-day mortality HR (95% CI) of 0.86 (0.81–0.91) and 0.85 (0.81–0.89), respectively. Hydrophilic statin users compared to lipophilic users had a 30-day and 90-day mortality HR (95% CI) of 0.90 (0.81–1.01) and 0.86 (0.78–0.94), respectively. Compared to simvastatin, 30-day mortality HRs (95% CI) were 0.85 (0.66–1.10), 0.87 (0.82–0.92), 0.87 (0.76–0.98), and 1.22 (1.10–1.36) for rosuvastatin, atorvastatin, pravastatin, and lovastatin, respectively. Conclusion. Statin use was associated with lower mortality in patients hospitalized with sepsis. Hydrophilic and synthetic statins were associated with better outcomes than lipophilic and fungal-based preparations.